The prevalence, genetic diversity and evolutionary analysis of cachavirus firstly detected in northeastern China - Nuowa Li; Nuowa Li; Yue Bai; Xin Yan; Zhiyuan Guo; Kongrui Xiang; Zaixing Yang; Haikun Shangguan; Junwei Ge; Junwei Ge; Lili Zhao (Frontiers in Veterinary Science, 2023)
Canine cachavirus is a novel parvovirus belonging to the genus Chaphamaparvovirus that was first detected in dogs in the United States. However, our knowledge of the prevalence and genetic characteristics of cachavirus is relatively limited. In this study, 325 canine fecal specimens collected from healthy and diarrheic dogs in northeastern China were screened with PCR. Twenty-two of the 325 (6.8%) samples were positive for cachavirus. The diarrhea samples showed high viral coinfection rates, and we detected coinfections with canine astrovirus (CaAstV) and cachavirus for the first time. A sequence analysis revealed that the Chinese cachavirus strains have point mutations in four consecutive amino acid codons relative to the original American strain. A codon usage analysis of the VP1 gene showed that most preferred codons in cachavirus were A- or T-ending codons, as in traditional canine parvovirus 2. A co-evolutionary analysis showed that cachavirus has undergone cospeciation with its hosts and has been transmitted among different host species. Our findings extend the limited cachavirus sequences available, and provide detailed molecular characterization of the strains in northeastern China. Further epidemiological surveillance is required to determine the significance and evolution of cachavirus.